We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
149
1
avatar+20 

 

thank you for the help

 

 

 Aug 26, 2018
 #1
avatar+100587 
+2

(5ab)^(2/3)  =

(5^2 * a^2 * b^2) ^(1/3) =

3√ [ 25 a^2 b^2 ]

 

3√ [ 27 x^6 y^3 ]  =

( 3^3 * x^6 * y^3)^(1/3) =    [use the fact that   (a^m)^n  =  a^(m*n)

(3 * x^2 * y)

 

 

cool cool cool

 Aug 26, 2018

8 Online Users

avatar